1985
DOI: 10.1073/pnas.82.18.6352
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-trisphosphate: a possible chemical link in excitation-contraction coupling in muscle.

Abstract: The role of inositol 1,4,5-trisphosphate (InsP3) in excitation-contraction coupling in skeletal muscle was investigated by several methods. The following results were obtained. InsP3 is released by electrical stimulation of muscles. Exogenous InsP3 releases calcium from skinned muscle fibers at relatively high doses under normal conditions but does so at very low concentrations when blockers of the InsP3 5-phosphatase are present. Blockers of InsP3 release are effective blockers of calcium transients elicited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(141 citation statements)
references
References 34 publications
8
132
1
Order By: Relevance
“…This is in good agreement with our calculated density of q~ charge movements. Alternatively, the voltage-sensor in the transverse tubule membrane could be a molecule that produces or releases a transmitter, perhaps inositol 1,4,5-triphosphate (Vergara et al, 1985), which would then act to open sarcoplasmic reticulum calcium channels. The observation that 0.5 mM tetracaine apparently inhibits phosphatidylinositol phosphorylation in transverse tubule membranes isolated from frog skeletal muscles is in agreement with this idea (Hidalgo et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This is in good agreement with our calculated density of q~ charge movements. Alternatively, the voltage-sensor in the transverse tubule membrane could be a molecule that produces or releases a transmitter, perhaps inositol 1,4,5-triphosphate (Vergara et al, 1985), which would then act to open sarcoplasmic reticulum calcium channels. The observation that 0.5 mM tetracaine apparently inhibits phosphatidylinositol phosphorylation in transverse tubule membranes isolated from frog skeletal muscles is in agreement with this idea (Hidalgo et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This was indeed found to be the case, at least in vitro. It was shown that physiological concentrations of spermine and spermidine inhibited a phospholipase C-dependent hydrolysis of phosphoinositides in rat brain (Eichberg et al, 1981) and in platelets (Nahas & Graff, 1982) (Israels et al, 1986 Vergara et al (1985) concluded that spermine was able to induce a blockage of the Ca2" signals in electrically stimulated muscle fibres by interfering with the formation of Ins(1,4,5)P. Ins( 1 ,4,5)P3 5-phosphatase is a key enzyme which metabolizes the second messenger into the inactive Ins(1,4)P2 and thus terminates its action on Ca2" mobilization. This enzyme, which is predominantly particulate and associated with the plasma membrane, was found blocked by spermine at near physiological concentrations (Seyfred et al, 1984).…”
Section: Polyamines and Transportmentioning
confidence: 99%
“…The evidence in favour of Ins(1,4,5)P3 may be summarized as follows: (a) Ins(1,4,5)P3 releases Ca2 + both from isolated SR terminal cisternae [234] and from skinned fibre preparations [234, 235, 241 -2441; (b) the entire machinery for the synthesis of the Ins(1,4,5)P3 precursor PtdIns(4,5)P2, Ins( 1 ,4,5)P3 formation (G-proteindependent phospholipase C) and Ins(1 ,4,5)P3 degradation [Ins(l ,4,5)P3 5-phosphatase] is present in the plasma membrane of striated muscles [245][246][247][248] and in a few cases, a selective enrichment of these synthetic and metabolic pathways has been found in T-tubules [245, 2481; (c) Ins(1,4,5)P3 levels increase dramatically upon electrical stimulation of skeletal muscles [235]; (d) Ins(1 ,4,5)P3, at micromolar concentrations, increases the opening probability of the Ca2 +-release channel of the SR after vesicle fusion with lipid bilayers [249]. A number of objections have been raised against the physiological role of Ins(1,4,5)P3 as a mediator in EC coupling in striated muscle, the most important being: (a) the release of Ca2 + from skinned skeletal muscle fibers activated by photohydrolyzed Ins(1 ,4,5)P3 is orders of magnitude slower than that observed under physiological conditions [250]; (b) the formation of Ins(1,4,5)P3 in electrically stimulated cells is observed only after tetanus [235]; (c) fiber contraction is not blocked by heparin, a known inhibitor preventing Ins(1 ,4,5)P3 binding to its receptor in smooth muscle and in non-muscle cells [251]. However, a high rate of contractions can be obtained by pressure injection of Ins(1,4,5)P3 [252] and heparin has no effect on the Ins(1 ,4,5)P3-induced contraction and Ca2+ release in skinned skeletal muscle fibers [253].…”
mentioning
confidence: 99%